Peningkatan Perkembangan Bahasa Aud Melalui Permainan “Celemek Bimsalabim” Di Tk Shafiya Smart School Tahun Ajaran 2021/2022 - Titik Rahayu Ningsih; Sri Haryanto; Hidayatu Munawaroh (Tinta Emas: Jurnal Pendidikan Islam Anak Usia Dini, 2022)
Language development is one of the most critical developments in Early Childhood (AUD) because language development is one of the abilities to master communication tools orally, in writing, or using signs. However, with the various problems faced by children in Shafiya Smart School Kindergarten, researchers are interested in researching the development of AUD language through the game "Aprons Bisalabim" in Shafiya Smart School Kindergarten. This study aims to improve the language development of Early Childhood in Shafiya Smart School Kindergarten because, in fact, the development of Early Childhood language in Shafiya Smart School Kindergarten still needs to be improved. This type of research uses a quantitative approach with experimental methods. The research sample consisted of 10 children. Data collection techniques using observation, interviews, documentation, and tests. And the data analysis technique used an analysis prerequisite test (normality test and homogeneity test) and a hypothesis test (descriptive statistics, gain test, and T-test). Thus, the game "Celemek Bimsalabim" can be used to improve the development of the AUD language.